Use of Amphetamine-Type Stimulants Among Emergency Department Patients With Untreated Opioid Use Disorder - Chawarski, Marek C. (Ann Emerg Med, 2020)
STUDY OBJECTIVE: Concurrent use of amphetamine-type stimulants among individuals with opioid use disorder can exacerbate social and medical harms, including overdose risk. The study evaluated rates of amphetamine-type stimulant use among patients with untreated opioid use disorder presenting at emergency departments in Baltimore, MD; New York, NY; Cincinnati, OH; and Seattle, WA. METHODS: Emergency department (ED) patients with untreated opioid use disorder (N=396) and enrolled between February 2017 and January 2019 in a multisite hybrid type III implementation science study were evaluated for concurrent amphetamine-type stimulant use. Individuals with urine tests positive for methamphetamine, amphetamine, or both were compared with amphetamine-type stimulant–negative patients. RESULTS: Overall, 38% of patients (150/396) were amphetamine-type stimulant positive; none reported receiving prescribed amphetamine or methamphetamine medications. Amphetamine-type stimulant–positive versus –negative patients were younger: mean age was 36 years (SD 10 years) versus 40 years (SD 12 years), 69% (104/150) versus 46% (114/246) were white, 65% (98/150) versus 54% (132/246) were unemployed, 67% (101/150) versus 49 (121/246) had unstable housing, 47% (71/150) versus 25% (61/245) reported an incarceration during 1 year before study admission, 60% (77/128) versus 45% (87/195) were hepatitis C positive, 79% (118/150) versus 47% (115/245) reported drug injection during 1 month before the study admission, and 42% (62/149) versus 29% (70/244) presented to the ED for an injury. Lower proportions of amphetamine-type stimulant–positive patients had cocaine-positive urine test results (33% [50/150] versus 52% [129/246]) and reported seeking treatment for substance use problems as a reason for their ED visit (10% [14/148] versus 19% [46/246]). All comparisons were statistically significant at P<.05 with the false discovery rate correction. CONCLUSION: Amphetamine-type stimulant use among ED patients with untreated opioid use disorder was associated with distinct sociodemographic, social, and health factors. Improved ED-based screening, intervention, and referral protocols for patients with opioid use disorder and amphetamine-type stimulant use are needed.